Amblopusa magna sp. n. - eine neue Art der amphipazifischen Gattung Amblopusa Casey, 1893 aus dem Fernen Osten Rußlands und ihre Stellung im phylogenetischen System (Coleoptera: Staphylinidae, Aleocharinae, Liparocephalini). Beiträge zur Kenntnis der ostpaläarktischen Insekten (6). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1998)
A catalogue of the genus Amblopusa which was revised by Ahn & Ashe (1996a, b) is delt with. The lectotype of brevipes and two paratypes of pacifica have been studied. The status of pacifica is discussed. It represents a valid species, not a synonym of brevipes. Diagnostic characters to distinguish pacifica and brevipes are given. Amblopusa magna sp. n. from the southern part of the Far East of Russia is described as new and compared with the other Amblopusa species. A modified phylogenetic system for the genus is proposed. Nomenclatural Acts brevipes Casey, 1893 (Amblopusa), Lectotype magna Zerche, 1998 (Amblopusa), spec. n. pacifica (K. Sawada, 1991) (Amblopusa), stat. rev. described as Boreorhadinus pacificus, hitherto a syn. of Amblopusa brevipes Casey, 1893